Pengembangan Kurikulum PAI : Kajian atas Ayat-Ayat Pendidikan Tauhid dalam Kitab Tafsir Al-Qur’an - Marshanda Rosy Rahmawati; Cucu Surahman; Elan Sumarna (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2025)
The concept of tauhid is a fundamental foundation in Islamic teachings that underpins all religious practices and spiritual understanding. In Islamic Religious Education (PAI), the teaching of tauhid is not merely theoretical but is also internalized in students' daily lives. This study highlights the importance of the aspects of rububiyah and uluhiyah in shaping the character of students, where they are invited to understand Allah as the Creator and the only God worthy of worship. Through teachings relevant to real-life situations, students are expected to develop gratitude, responsibility, and noble character. The Qur'an, as the primary source of tauhid education, provides verses that serve as references, such as Surah Al-Ikhlas and Al-Baqarah, emphasizing the oneness of Allah. In developing a tauhid-based PAI curriculum, a holistic approach and effective teaching methods, including the use of technology, are essential. However, challenges in implementing tauhid education, such as a lack of understanding among educators and an unsupportive environment, must be addressed through collaboration with parents and the community. Recommendations for curriculum development are expected to strengthen the integration of tauhid values, enabling students to not only acquire knowledge but also embody good character and responsibility